2020
DOI: 10.1016/j.phymed.2020.153333
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine and hydroxychloroquine as ACE2 blockers to inhibit viropexis of 2019-nCoV Spike pseudotyped virus

Abstract: Background The novel coronavirus disease (2019-nCoV) has been affecting global health since the end of 2019 and there is no sign that the epidemic is abating . The major issue for controlling the infectious is lacking efficient prevention and therapeutic approaches. Chloroquine (CQ) and Hydroxychloroquine (HCQ) have been reported to treat the disease, but the underlying mechanism remains controversial. Purpose The objective of this study is to investigate whether CQ and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…In an earlier study, a compound coined SSAA09E2 has been shown to block the binding of the SARS-CoV spike protein to ACE2 and to inhibit SARS-CoV infection in ACE2 expressing HEK-293T cells with an EC 50 of 3.1 μM ( Adedeji et al, 2013 ). Chloroquine and hydroxychloroquine, in addition to their pH elevating effects in endosomes, bind to ACE2 ( N. Wang et al, 2020 ), impair the terminal glycosylation of ACE2 ( Vincent et al, 2005 ) and inhibit SARS-CoV replication ( Al-Bari, 2017 ; Keyaerts, Vijgen, Maes, Neyts, & Van Ranst, 2004 ). They also prevent the entrance of SARS CoV-2 spike protein into ACE2 expressing cell lines (N. Wang et al, 2020).…”
Section: Antiviral Agents and Other Drugs On Ace2mentioning
confidence: 99%
“…In an earlier study, a compound coined SSAA09E2 has been shown to block the binding of the SARS-CoV spike protein to ACE2 and to inhibit SARS-CoV infection in ACE2 expressing HEK-293T cells with an EC 50 of 3.1 μM ( Adedeji et al, 2013 ). Chloroquine and hydroxychloroquine, in addition to their pH elevating effects in endosomes, bind to ACE2 ( N. Wang et al, 2020 ), impair the terminal glycosylation of ACE2 ( Vincent et al, 2005 ) and inhibit SARS-CoV replication ( Al-Bari, 2017 ; Keyaerts, Vijgen, Maes, Neyts, & Van Ranst, 2004 ). They also prevent the entrance of SARS CoV-2 spike protein into ACE2 expressing cell lines (N. Wang et al, 2020).…”
Section: Antiviral Agents and Other Drugs On Ace2mentioning
confidence: 99%
“…In fact, both inhibit the SARS-CoV-2 viral replication [ 8 ], decrease antigen processing and its presentation [ 9 , 10 ], and decrease the cellular activity via low secretion of inflammatory cytokines and type 1 interferon [ 5 ]. CQ and HCQ might also interfere with angiotensin-converting enzyme 2 (ACE2) receptor which is involved in COVID-19 and its symptoms [ 11 ]. Strong interactions have been reported between the SARS-CoV-2 RBD domain of the S protein and ACE2 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…ACE2-overexpressing HEK293T cell (ACE2-HEK293T) line was constructed by Genomeditech (Shanghai, China) and its over-expression of ACE2 has been verified in our previous research ( Wang et al, 2020 ). ACE2-HEK293T was cultured at 37 °C and 5% CO 2 in Dulbecco's modification of eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 100 U/ml penicillin, 100 μg/ml streptomycin, and 4 μg/ml puromycin.…”
Section: Methodsmentioning
confidence: 94%